KAJIAN TENTANG KEDUDUKAN AGUNAN DALAM AKAD PEMBIAYAAN MUDHARABAH PADA BANK SYARIAH - Irawan, Vendra (Alhurriyah, 2019)
AbstractThe purpose of this research is to examine the position of collateral in the mudharabah financing contract in Islamic banking. The type of research used is normative research with a statute approach and a conceptual approach. The sources of legal material in this study are from primary legal material and secondary legal material. The results of the analysis of this study are that the collateral position in the mudharabah contract in Islamic banking is different from the position of collateral in conventional banking, collateral in conventional banking functions as guarantor of the debts that occur between creditors and debtors. While the function of collateral in the mudharabah agreement on Islamic banking is to ensure the implementation of the mudharabah agreement in accordance with the agreement made in the beginning of the agreement between capital owners and business manager. So, the purpose of collateral in mudharabah contract is to avoid bad moral of business manager and not to return the investment value if there is a loss due to business risk factors.Keywords: Position; Collateral; Mudharabah; Islamic BankAbstrakPenelitian ini bertujuan untuk mengkaji kedudukan agunan dalam akad pembiayaan mudharabah pada perbankan syariah. Jenis penelitian yang digunakan adalah penelitian normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Sumber bahan hukum dalam penelitian ini adalah dari bahan hukum primer dan bahan hukum sekunder. Hasil analisis dari penelitian ini adalah kedudukan agunan pada akad mudharabah di perbankan syariah berbeda dengan kedudukan agunan pada perbankan konvensional, agunan pada perbankan konvensional berfungsi sebagai penjamin atas utang-piutang yang terjadi antara kreditur dengan debitur. Sedangkan fungsi agunan dalam akad mudharabah pada perbankan syariah adalah untuk menjamin terlaksananya akad mudharabah sesuai dengan kesepakatan yang telah dibuat diawal perjanjian antara shahib al-maal dengan mudharib. Jadi, tujuan agunan dalam akad mudharabah adalah untuk menghindari moral jelek mudharib dan bukan untuk mengembalikan nilai investasi jika terjadi kerugian karena faktor risiko bisnis.Kata kunci: Kedudukan; Agunan; Mudharabah; Bank Syariah